Sex Hormones and Processing of Facial Expressions of Emotion: A Systematic Literature Review - Osório, Flávia L.; de Paula Cassis, Juliana M.; Machado de Sousa, João P.; Poli-Neto, Omero; Martín-Santos, Rocio (Frontiers in Psychology, 2018)
Background: We systematically reviewed the literature to determine the influence of sex hormones on facial emotion processing (FEP) in healthy women at different phases of life. Methods: Searches were performed in PubMed, Web of Science, PsycINFO, LILACS, and SciELO. Twenty-seven articles were included in the review and allocated into five different categories according to their objectives and sample characteristics (menstrual cycle, oral contraceptives, pregnancy/postpartum, testosterone, and progesterone). Results: Despite the limited number of studies in some categories and the existence of inconsistencies in the results of interest, the findings of the review suggest that FEP may be enhanced during the follicular phase. Studies with women taking oral contraceptives showed reduced recognition accuracy and decreased responsiveness of different brain structures during FEP tasks. Studies with pregnant women and women in the postpartum showed that hormonal changes are associated with alterations in FEP and in brain functioning that could indicate the existence of a hypervigilant state in new and future mothers. Exogenous administration of testosterone enhanced the recognition of threatening facial expressions and the activation of brain structures involved in the processing of emotional stimuli. Conclusions: We conclude that sex hormones affect FEP in women, which may have an impact in adaptive processes of the species and in the onset of mood symptoms associated with the premenstrual syndrome.